2006
DOI: 10.1007/s10545-006-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure in pregnancy associated with maternal MCAD deficiency

Abstract: In recent years the association between severe pregnancy complications and fetal fatty acid oxidation (FAO) disorders has been reported. However, there are few descriptions of a maternal FAO disorder leading to these complications. We describe acute liver failure associated with an undiagnosed maternal medium-chain acyl-CoA dehydrogenase (MCAD) deficiency. The previously healthy proband presented at the 39th week with an itchy rash, palmar erythema and trace proteinuria; she was admitted onto a maternity ward.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…6 Santos et al reported a case of undiagnosed maternal MCAD deficiency presenting with acute liver failure during pregnancy. 17 A 29-year-old Caucasian primigravida felt unwell during pregnancy and had poor oral intake. In the 39th week, blood analysis showed signs of hepatopathy, and acute fatty liver was suspected leading to Caesarean section and delivery of a healthy boy.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Santos et al reported a case of undiagnosed maternal MCAD deficiency presenting with acute liver failure during pregnancy. 17 A 29-year-old Caucasian primigravida felt unwell during pregnancy and had poor oral intake. In the 39th week, blood analysis showed signs of hepatopathy, and acute fatty liver was suspected leading to Caesarean section and delivery of a healthy boy.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Acute liver failure in pregnancy might have occurred coincidentally with MCAD deficiency, but it cannot be ruled out as the underlying condition triggering an unusual presentation. 17 Since there are no subtle specific symptoms or signs of MCAD deficiency that could help physicians suspect this disease before patients present with severe hypoglycemic coma and its consequences, NBS for MCAD deficiency is essential to detect affected individuals. 3,[18][19][20][21][22][23][24][25][26] The introduction of tandem mass spectrometry (MS/MS) NBS programs in the 1990s have helped to reduce metabolic crisis and death in MCAD deficiency.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…There are a few reports that suggest that other enzymes of FAO may be involved as well [179,182]. Fetal hepatic carnitine palmytoiltransferase (CPT I) deficiency was reported to cause maternal AFLP in two successive pregnancies.…”
Section: Pathogenesismentioning
confidence: 99%
“…There is one case report of recurrent AFLP and hyperemesis gravidarum in two successive pregnancies in a patient whose offspring were diagnosed with CPT I deficiency [183]. A different author reported pre-existing undiagnosed maternal medium-chain acyl-CoA dehydrogenase (MCAD) deficiency in the patient with AFLP, who delivered a baby without enzyme abnormalities [182]. The results of a study that looked at the incidence of maternal liver disease in pregnancies with fetal FAO defects suggested that fetal longchain defects are 50 times more likely to develop a liver disease in pregnancy when compared with healthy controls; and short-and medium-chain FAO defects are 12 times more likely to develop liver disease [179].…”
Section: Pathogenesismentioning
confidence: 99%
“…CPT2 deficiency, MCADD and VLCADD have been described in several case reports (Ramsey and Biggio 2005;Santos et al 2007;Yamamoto et al 2015).…”
Section: Introductionmentioning
confidence: 96%